The Influence of Students' Financial Understanding and Life Style on Interest in Using Technology-Based Loans (Pinjol) in the Era of Financial Services Digitalization : Case Study on Students at Solo Raya University - Dinda Mutiara Astuty; Susilaningtyas Budi Kurniawati; Syahriar Abdullah (International Journal Business, Management and Innovation Review, 2025)
This study aims to analyze the influence of students' financial understanding and lifestyle on interest in using technology-based loans or online loans. Due to the ease of access to financial services in this era of digitalization, students have a variety of options to meet their financial needs, including online loans. This study uses a quantitative approach and uses primary data through questionnaires that are distributed to students as respondents. The results of the research analysis showed that financial understanding did not have a significant effect on the interest in using online loans, while on the contrary, lifestyle had a significant effect on the interest in using online loans. These findings show that students' tendency to consumptive lifestyles or lifestyle behavior patterns determine their interest in using online loans compared to financial literacy levels. Therefore, wise lifestyle management needs to be the focus in efforts to educate students so that the use of loan services can be carried out responsibly.